Developmental toxicity of dimethachlor during zebrafish embryogenesis mediated by apoptosis and oxidative stress - Garam An; Hahyun Park; Gwonhwa Song; Whasun Lim (The Korean Society of Animal Reproduction and Biotechnology, 2021)
Dimethachlor is a synthetic herbicide, belonging to the chloroacetanilide group, that inhibits the undesirable growth of weeds via the suppression of very longchain fatty acid synthesis. Although dimethachlor has been shown to run off from agricultural fields into aquatic ecosystems, the toxicity of dimethachlor on aquatic invertebrates and vertebrates is unknown. In our study, we assessed the toxicity of dimethachlor on developing zebrafish embryos by analyzing viability, hatching ability, and phenotypic changes. Embryonic viability decreased from 48 h post-fertilization (hpf) at the highest concentration of dimethachlor. Decreased hatching ratio, shortened body length, and pathological changes in the eye, heart, and yolk sac were observed at sub-lethal concentrations. Additionally, dimethachlor increased the number of apoptotic cells and level of reactive oxygen species 120 hpf. Our results indicate that dimethachlor may act as an anti-developmental toxicant when accumulated in an aquatic environment.Dimethachlor is a synthetic herbicide, belonging to the chloroacetanilide group, that inhibits the undesirable growth of weeds via the suppression of very longchain fatty acid synthesis. Although dimethachlor has been shown to run off from agricultural fields into aquatic ecosystems, the toxicity of dimethachlor on aquatic invertebrates and vertebrates is unknown. In our study, we assessed the toxicity of dimethachlor on developing zebrafish embryos by analyzing viability, hatching ability, and phenotypic changes. Embryonic viability decreased from 48 h post-fertilization (hpf) at the highest concentration of dimethachlor. Decreased hatching ratio, shortened body length, and pathological changes in the eye, heart, and yolk sac were observed at sub-lethal concentrations. Additionally, dimethachlor increased the number of apoptotic cells and level of reactive oxygen species 120 hpf. Our results indicate that dimethachlor may act as an anti-developmental toxicant when accumulated in an aquatic environment.